2020
DOI: 10.1177/0162643420976167
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Computerized Sentence and Paragraph Strategy Instruction for Struggling Adolescent Writers

Abstract: The purpose of this study was to determine whether struggling adolescent writers could learn sentence and paragraph writing skills from a software program. Nine junior-high and nine senior-high struggling writers participated in a multiple-probe across-students design that was replicated six times. Instructional procedures within the software program were based on methods previously found to be successful in teaching learning strategies to adolescents. Measures included scores on practice activities, time spen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Thus, a logical notion that follows these findings is that social skills instruction might be one intervention of choice, not only to address behavior problems but also to improve interpersonal skills (Durlak et al, 2011;Gresham, 1998;Gresham et al, 2001;Mathur & Rutherford, 1994;Mathur et al,1998;Osher et al, 2008;, Vernon et al, 1996, 2020. Loeber and Farrington (1998), for example, suggested that the most effective treatments for youth with adjustment problems incorporated interpersonal skill training.…”
Section: Social Skills Instruction As An Optionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a logical notion that follows these findings is that social skills instruction might be one intervention of choice, not only to address behavior problems but also to improve interpersonal skills (Durlak et al, 2011;Gresham, 1998;Gresham et al, 2001;Mathur & Rutherford, 1994;Mathur et al,1998;Osher et al, 2008;, Vernon et al, 1996, 2020. Loeber and Farrington (1998), for example, suggested that the most effective treatments for youth with adjustment problems incorporated interpersonal skill training.…”
Section: Social Skills Instruction As An Optionmentioning
confidence: 99%
“…Some researchers have shown that these instructional methods can be incorporated into interactive multimedia (IM) programs to teach academic skills (e.g., Lancaster et al, 2006Lancaster et al, , 2009Schumaker, 2020;Schumaker et al, 2019aSchumaker et al, , 2019b) and social skills. With regard to social skills, Lancaster et al (2002) conducted a study whereby students with learning disabilities (LD) were taught self-advocacy skills to be used in Individualized Education Program (IEP) meetings with an IM program.…”
Section: Multimedia Instruction As a Solutionmentioning
confidence: 99%
“…SWDs need (1) explicit instruction to support their development as writers (Harris & McKeown, 2022), (2) an established writing routine (Slavin et al, 2019), (3) designated time for writing (Troia, 2014), (4) feedback on their writing (Troia, 2014), and (5) the opportunity to set goals for their writing (Slavin et al, 2019). Researchers have identified that strategy instruction effectively provides the additional supports SWDs need (Schumaker, 2022). Strategy instruction for writing provides a process approach for students to follow (Troia, 2014) with four critical components: (1) explicitly explaining the rationale and purpose for the strategy, (2) modeling how the strategy is used, (3) providing opportunities to practice and apply the strategy, and (4) adapting the strategy for the assignment and student needs (Graham & Harris, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Strategy instruction for writing provides a process approach for students to follow (Troia, 2014) with four critical components: (1) explicitly explaining the rationale and purpose for the strategy, (2) modeling how the strategy is used, (3) providing opportunities to practice and apply the strategy, and (4) adapting the strategy for the assignment and student needs (Graham & Harris, 2019). Strategy instruction for writing can include the Self-Regulated Strategy Development (SRSD) suite of strategies (Graham et al, 2019b) or the Strategic Instruction Model (SIM) Strategies (Schumaker, 2022).…”
Section: Introductionmentioning
confidence: 99%